Drivers, enablers, and challenges of effective project managers / Noornina Md Dahlan ...[et al.] - Md Dahlan, Noornina; Mat Din, Syaidatul Zarina; Md Dahlan, Noornina; Dahlan, Jaslin Md; Zainuddin, Noor Azrin (UiTM Cawangan Johor, 2019)
The purpose of this research is to examine the drivers, enablers, and challenges of an effective project manager. This is a quantitative research study target consist of project managers, project leads, managers and as well as project contributors who work in any company in Malaysia. A total of 250 questionnaires have been distributed via email and hard copies to the major industry state in Malaysia like Penang, Kuala Lumpur and Johor. Resulted in 133 questionnaires or 53.2% of completed questionnaires were returned and used for statistical analysis. The analysis indicates that in knowledge and skill dimension like a soft skill, technical skill, and green skill play an important role to drive and enables the effectiveness of a project manager. Besides, tools and techniques used and applied during project planning, monitoring and controlling also show a significant component in determining the effectiveness of a project manager. Surprisingly, in the innovativeness dimension project manager with innovator characteristic show did not have significant influence for an effective project manager however project manager with adaptor characteristic was shown significantly to be an effective project manager which contradicts with the previous literature study. As a conclusion, in order to remain competitive, these drivers, enablers, and challenges are essential for any organizations' project managers when managing and handling projects.